Model-based real-time robust controller for a small helicopter. (1st January 2021) - He, Miaolei; He, Jilin; Scherer, Sebastian
Highlights: A helicopter control system is nonlinear and has strong coupling and multi-inputmultioutput (MIMO) characteristics. This paper studies the modeling and flight controller design of a small helicopter. Based on a non-simplified helicopter model, a robust control law combined with a newly developed trajectory tracking controller is proposed. An easy way to realize stable control and trajectory control. Abstract: Small helicopters attract substantial attention because they feature better loading capacity and flight efficiency than multirotor helicopters. The main objective of this work is to study the modeling and flight controller design of a small helicopter. Based on a non-simplified helicopter model, a robust control law combined with a newly developed trajectory tracking controller is proposed. The inner loop uses a H∞ technique to ensure helicopter robust attitude tracking performance. The outer loop uses a prescribed performance control technique to guarantee the position controller output error converges to a pre-defined arbitrary residual set. The convergence rate of out loop will be no less than a certain prespecified value, and any overshoot will be below a preassigned level. The proposed control algorithm was tested on a real helicopter platform when the wind disturbance and system uncertainty exist, and the results demonstrate the effectiveness and robustness of our approach.